On the foundations of a new approach to statistical mechanics of classical systems - S. N. Bagghi (International Journal of Mathematics and Mathematical Sciences)
It has been known for a long time that the fundamental approaches to equilibrium and nonequillbrium statistical mechanics available at present lead to physical and mathematical inconsistencies for dense systems. A new approach, whose foundation lies in the more powerful statistical method of counting complexions, had been formulated which not only overcomes all these difficulties but also yields satisfactory physical results for dense 'hard sphere' systems as well as for systerns containing charged particles for which a mathematically consistent theory cannot even be formulated if we follow the available formalisms. The specific computational techniques rely on the following four recipes which also are justified theoretically.